2013
DOI: 10.5966/sctm.2013-0090
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postnatal Transplantation of Fetal Mesenchymal Stem Cells in Osteogenesis Imperfecta: A Two-Center Experience

Abstract: This study reports the clinical course of two patients with osteogenesis imperfecta who received prenatal human fetal mesenchymal stem cell (MSC) transplantation and postnatal boosting with same‐donor MSCs. Findings suggest that prenatal transplantation of allogeneic human fetal MSCs in osteogenesis imperfecta appears safe and is of likely clinical benefit and that retransplantation with same‐donor cells is feasible. Further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 44 publications
1
154
0
5
Order By: Relevance
“…(105) Previous human studies of bone marrow transplantation showed little mesenchymal lineage engraftment and failed to deliver clear benefit, (106,107) but the recent report of fetal stem cell infusion both before and after delivery in a child thought to have type IV OI was encouraging. (108) Ex vivo manipulation of cells and then their reintroduction has been widely discussed after the recent successful treatment of a child with leukemia. In OI, an approach of this type could substantially impact on tissue phenotype.…”
Section: Effects Of Current Interventions In Oimentioning
confidence: 99%
“…(105) Previous human studies of bone marrow transplantation showed little mesenchymal lineage engraftment and failed to deliver clear benefit, (106,107) but the recent report of fetal stem cell infusion both before and after delivery in a child thought to have type IV OI was encouraging. (108) Ex vivo manipulation of cells and then their reintroduction has been widely discussed after the recent successful treatment of a child with leukemia. In OI, an approach of this type could substantially impact on tissue phenotype.…”
Section: Effects Of Current Interventions In Oimentioning
confidence: 99%
“…Götherström ve ark. [39] 2014 yılında bildirdikleri klinik çalımalarında prenatal ve postnatal olarak ortak donörden alınan MKH retransplantasyonu uygulamılardır. Aratırmacılar 2.8x10 6 hücre/kg olarak uyguladıkları tedavi sonrası düük seviyede kemik engraftmanı, lineer büyüme, kırık ve mobilite de iyileme saptadıklarını bildirmilerdir.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified
“…Sonuçlar do¤rultusunda prenatal ve postnatal OI tespit edilen olgulara allojenik MKH retransplantasyonunun güvenilir ve etkili oldu¤unu bildirilmitir. [39] Osteoartrit tedavisinde, allojenik kemik ili¤i kaynaklı MKH'nin denendi¤i bir baka çalımada primer hastalıkları radyolojik bulgularla gösterilmi 30 hasta iki gruba ayrılmı, kontrol grubuna hyaluronik asit (60 mg tek doz), deney grubu hastalarına ise yine eklem içi 40x10 6 MKH uygulanmı. Bir yıl sonraki kontrollerde a¤rı, yaam kalitesi ve hareket kısıtlılı¤ında azalma oldu¤u kaydedilmi.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified
“…The patient co-received vitamin D3, calcium and bisphosphonates. Unfortunately, he died at the age of 5 months as a result of respiratory failure associated with pneumonia [18].…”
Section: Mesenchymal Stem Cells In Regenerative Medicinementioning
confidence: 99%